2014
DOI: 10.1515/jbcpp-2014-0019
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of aqueous extract of Mangifera indica in Wistar rats

Abstract: The results of this preliminary investigation suggest that MI contains active compounds with an anti-inflammatory activity. However, more detailed studies using additional models are necessary to further characterise the effects of MI in inflammatory disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Moreover, a recent intervention study in humans reported moderate beneficial effects of the same mango fruit powder on microcirculation and endothelial function [18], mediated, at least partly, by the activation of endothelial nitric oxide synthase [18]. Similar results from studies with rats [15] and human umbilical vein cells [20] also suggest that polyphenols of aqueous extracts of Mango may protect endothelial cells. These results are of interest considering that impaired microvascular function is observed early in the development of type 2 diabetes mellitus and cardiovascular disease [21].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, a recent intervention study in humans reported moderate beneficial effects of the same mango fruit powder on microcirculation and endothelial function [18], mediated, at least partly, by the activation of endothelial nitric oxide synthase [18]. Similar results from studies with rats [15] and human umbilical vein cells [20] also suggest that polyphenols of aqueous extracts of Mango may protect endothelial cells. These results are of interest considering that impaired microvascular function is observed early in the development of type 2 diabetes mellitus and cardiovascular disease [21].…”
Section: Introductionmentioning
confidence: 85%
“…is a globally consumed fruit with reported health-promoting properties [10-13] and, based on studies in rats [14, 15] and humans [16, 17], its habitual consumption may contribute to the prevention of diabetes mellitus, obesity, and related complications. In addition, it has been reported that the food ingredient Careless TM , a 100% pure mango fruit powder characterized by a high content in secondary plant metabolites, including gallic acid, rutin and mangiferin (MGF) [18], activates sirtuin 1 (SIRT1) and AMP-activated protein kinase (AMPK) in cell systems [19], which are both involved in energy homeostasis and glucose and lipid metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Africa is enriched with pharmacological agents that target various diseases, [82][83][84][85][86][87][88] and they can produce supportive roles for gene therapy treatments to produce precision treatments. Precision medicine aims to tailor treatment specific to an individual, or groups of patients sharing the same disease characteristics, and it relies on the use of diagnostic testing, studies and analysis to find accurate treatments.…”
Section: The Relevance Of the Novel Hi Genes To Precision Medicine In...mentioning
confidence: 99%